Avaliação do desenvolvimento pulmonar em crianças prematuras do primeiro ano de vida à idade escolar - Bastos, Vinícius Gonçalves (2012)
The lung function of preterm infants is reduced and there are several pre-and postnatal factors associated with lower flow. There is extensive material on the effects of prematurity on lung function in early life, but little has been studied over the long term outcomes. This study therefore has the objective to describe lung development in premature infants, using data collected in the first year of life and correlating these data with functional tests obtained years later. To address this question we conducted a cohort study, prospective, where examinations were performed pulmonary function in infants in a group of children born prematurely, before the first year of life, and after some years the children were again subjected to spirometry to assess and performing development lung compared to the results of the first test. 40 children underwent lung function testing of infants (first test) and 37 children performed the second test. Of the 40 subjects, 17 (42%) were male, and 25 (63%) were white, the variation of Z scores for FVC and FEF2575 between the two tests showed statistically significant increase (p from 0.028 to 0.016). The predictor variables that influenced these changes were gender (male sex) and infection pre-and postnatal (chorioamnionitis and early sepsis). In conclusion, our data suggest that there is a trend of accelerated growth of lung function between the first and fifth years of life for children born premature, both in volume and in pulmonary flow, suggesting that, in part, this growth is due to the regression to the mean. Exposure to infection in the neonatal period has a limited effect on lung function with reduction in expiratory flows during the first years of life. These abnormalities are not detected later in life